An online randomized trial of healthy default beverages and unhealthy beverage restrictions on children’s menus - Pasquale E. Rummo; Alyssa J. Moran; Aviva A. Musicus; Christina A. Roberto; Marie A. Bragg (Preventive Medicine Reports, 2020)
Several U.S. jurisdictions have adopted policies requiring healthy beverage defaults on children’s menus, but it is unknown whether such policies or restrictions leads to fewer calories ordered. We recruited 479 caregivers of children for an online choice experiment and instructed participants to order dinner for their youngest child (2–6 years) from two restaurant menus. Participants were randomly assigned to one type of menu: 1) standard beverages on children’s menus (Control; n = 155); 2) healthy beverages on children’s menus (water, milk, or 100% juice), with unhealthy beverages available as substitutions (Default; n = 162); or 3) healthy beverages on children’s menus, with no unhealthy beverage substitutions (Restriction; n = 162). We used linear regression with bootstrapping to examine differences between conditions in calories ordered from beverages. Secondary outcomes included percent of participants ordering unhealthy beverages (full-calorie soda, diet soda, and/or sugar-sweetened fruit drinks) and calories from unhealthy beverages. Calories ordered from beverages did not differ across conditions at Chili’s [Default: 97.6 (SD = 69.8); p = 0.82; Restriction: 102.7 (SD = 71.5); p = 0.99; Control: 99.4 (SD = 72.7)] or McDonald’s [Default: 90.2 (SD = 89.1); p = 0.55; Restriction: 89.0 (SD = 81.0); p = 0.94; Control: 96.5 (SD = 95.2)]. There were no differences in the percent of orders or calories ordered from unhealthy beverages. Though Restriction participants ordered fewer calories from full-calorie soda [(3.0 (SD = 21.6)] relative to Control participants [13.4 (SD = 52.1); p = 0.04)] at Chili’s, we observed no such difference between Default and Control participants, or across McDonald’s conditions. Overall, there was no effect of healthy default beverages or restrictions in reducing total calories ordered from unhealthy beverages for children in our experiment.